Peran Influencer, Citra Merek, dan Kualitas Produk Terhadap Minat Beli Pada E-commerce Shopee - Ilmiah, Qhifdina; Oetarjo, Mas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this modern era, technology has changed human life to become more practical in business activities. One of the breakthroughs is the existence of an e-commerce platform and the most popular among Indonesians is Shopee. The Shopee application cannot be separated from the role of influencers, brand image and product quality. This makes researchers want to examine what variables influence buying interest. The aim of this research is to find out what variables have an influence on increasing buying interest. This research uses quantitative methods with primary data types. Respondents in this study were determined using the Lemeshow formula and the respondents were 98 to 100 people. Data testing in this study used multiple linear regression analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, T test, and F test. The results of this study were that the three variables, namely influencer, brand image and product quality had an influence significantly influence consumer buying interest in Shopee e-commerce.